2021
DOI: 10.1016/j.rmed.2020.106276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical status and lung function 10 weeks after severe SARS-CoV-2 infection

Abstract: Since studies about clinical status after COVID-19 are scarce, we conducted a cross sectional study with assessment of residual symptoms, lung function and chest CT. Materials and Methods: During an outpatient follow-up visit, chest CT, pulmonary function and COVID-19 related symptoms were assessed approximately 10 weeks after diagnosis. Demographics, baseline (time of diagnosis) CT score and blood results were collected from patient files. Association between lung function and clinical characteristics (baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 11 publications
13
49
0
1
Order By: Relevance
“…A high proportion of patients remain symptomatic at 6–12 weeks after discharge, particularly with fatigue and breathlessness. These findings are similar to a recently reported central London cohort, 9 and to a Belgian study, 19 where a restrictive pattern of lung function was common (38%, N=84/101). This finding was associated with longer, or critical care admission.…”
Section: Discussionsupporting
confidence: 91%
“…A high proportion of patients remain symptomatic at 6–12 weeks after discharge, particularly with fatigue and breathlessness. These findings are similar to a recently reported central London cohort, 9 and to a Belgian study, 19 where a restrictive pattern of lung function was common (38%, N=84/101). This finding was associated with longer, or critical care admission.…”
Section: Discussionsupporting
confidence: 91%
“…The decision to discharge was made clinically based on patients’ clinical status and per hospital policy in the other 12 studies [ 20 – 31 ]. Among these studies, 13 studies collected data of chest CT [ 17 25 , 27 , 29 – 31 ] and 10 studies collected data of PFT [ 17 , 18 , 20 , 22 , 24 – 29 ] from the patients with COVID-19 discharged during their study period. Risk of bias of each study is shown in Additional file 1 : figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…13 studies were eligible to assess the residual chest CT findings [ 17 25 , 27 , 29 – 31 ]. The average approximate follow-up timing after either symptom onset or hospital discharge was 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary functional parameters, including diffusing capacity for carbon monoxide, were not found to be significantly different between patients with normal and abnormal perfusion except for FRC. Recent studies have suggested that reduced DLCO and TLC were the main abnormalities observed after COVID-19 [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%